MANAGEMENT OF EXTRACURRICULAR ACTIVITIES AT AL-HASYIMIYAH ISLAMIC BOARDING SCHOOL TEBING TINGGI - Wijaya, Candra; Sahputra, Edi; Rambe, Mirza Syadat (Universitas Dharmawangsa Medan, 2021)
ABSTRACTThis study aims to obtain a detailed description of (1) Planning extracurricular activities in character building of students (2) Organizing extracurricular activities in character building of students (3) Directing extracurricular activities in character building of students and (4) Controlling extracurricular activities in shaping the character of students at PPM Al-Hasyimiyah Tebing Tinggi. This study uses a qualitative approach, the type of phenomenological research, and the descriptive analysis method. Data collection techniques are carried out by; participatory observation, in-depth interviews, and document analysis. The data analysis process is carried out starting from; data reduction, data presentation, and conclusion. Test the validity of the data by triangulation and member checks. The results of this study are (1) Planning for extracurricular activities in the formation of students' character is carried out in the form of preparing extracurricular activity programs which are then used as a reference in its implementation. The program development process is preceded by an analysis of the required resources, collaboratively enforced, and socialized at the beginning of the school year. (2) Organizing extracurricular activities in forming the character of students as a whole is integrated with the madrasa organization. The organizing process consists of; determination of resources, the division of tasks according to their field of expertise, determined by the Decree of the Head of Madrasah, making agreements to shape the character of students through routine activities, for example, spontaneous action, and conditioning. (3) The direction of extracurricular activities in the formation of the character of students is carried out to ensure that the implementation of activities is directed at the goals that have been set in the planning. The briefing process includes; implementation of activities according to the plan, the pattern of activities includes (introduction, core, closing), teachers/coaches prioritize exemplary, effective leadership, problem-solving together, commitment to tasks, functions, and roles, (4) Control of extracurricular activities in the formation of student character implemented through; monitoring, assessment, and reporting. The control process includes; monitoring the implementation of activities, evaluating activities through process assessments and results assessments, the majority of students obtain satisfactory results, but still need to optimize the existing elements in planning, organizing, directing and controlling, and efforts to improve the readiness of the supporting components are needed.Keywords: Management, Extracurricular, Character